IBM DS8000 High-Performance Flash Enclosure Gen2 product guide - Dufrasne, Bertrand; Kimmel, Peter; Helmbrecht, Detlef (IBM Redbooks, 2020)
This IBM® Redpaper"!publication describes the IBM DS8880 High-Performance Enclosure (HPFE) Gen2 architecture and configuration, as of DS8900 Release 9.1. The IBM® DS8000® High-Performance Flash Enclosure Gen2 (HPFE Gen2) is a 2U storage enclosure that is installed in pairs in DS8900F and DS8880 models. The flash enclosure and Flash RAID adapters are installed in pairs. Each storage enclosure pair can support 16, 32, or 48 encryption-capable flash drives (2.5-inch, 63.5 mm form factor)
Date of publication from resource description page. - "Storage.". - Number on back cover: REDP-5422-03. - Includes bibliographical references. - Online resource; title from cover (Safari, viewed April 21, 2020)
Keywords: Storage area networks (Computer networks); IBM computers; Réseaux de stockage (Informatique); IBM (Ordinateurs)